Determinants of the cost of starting a business in Mexico - Erick Rangel González; Leonardo E. Torre Cepeda (Banco de México, 2014)
We construct a panel data at the state level in Mexico for the years 2006, 2008 and 2011 in order to investigate the impact that entry deregulation efforts have on the cost of opening new businesses in Mexico, where this cost is taken from the Doing Business in Mexico report of the World Bank. Using a model that the controls for the financial strength of the states, market profitability, regional fixed effects, and considering endogenous effects, we find that the measures of entry deregulation are strongly associated with a reduction in the cost of opening a new business.
Keywords: L88; O25; C33; O10; 330; Deregulation Cost of Opening New Businesses; Cost of Opening New Businesses; GDP per capita